Load carriage magnitude and locomotion strategy alter knee total joint moment during bipedal ambulatory tasks in recruit-aged women. (22nd May 2020) - Krajewski, Kellen T.; Dever, Dennis E.; Johnson, Camille C.; Rawcliffe, Alex J.; Ahamed, Nizam U.; Flanagan, Shawn D.; Mi, Qi; Anderst, William J.; Connaboy, Chris
Abstract: Knee osteoarthritis (OA) is prevalent among female soldiers, resulting in limited duty and long term adverse ambulatory effects. A proposed mechanism to the development of knee OA is the assiduous execution of load carriage tasks. Soldiers are often required to maintain a walking gait with load at velocities beyond their gait transition velocity (GTV) known as forced marching. The primary aim of this investigation is to determine the interactive effects of load magnitude and locomotion pattern on relative knee total joint moment (KTJM) in healthy recruit-aged women. The secondary aims are to determine knee total joint moment limb differences and to determine the interactive effect of load magnitude and locomotion pattern on the percent contributions of each plane of motion moment. Individuals were tasked with running and forced marching at 10% above their GTV at body weight (BW) and with an additional 25% and 45% of their BW. KTJM was analyzed at two specific gait events of heel-strike and mid-stance. At heel-strike, forced marching exhibited greater KTJM compared to run for all load conditions but running had greater KTJM than forced marching at mid-stance. The forced marching pattern exhibited larger KTJM for the dominant limb at both gait events compared to running. Lastly, at mid-stance the knee adduction moment percent (KAM%) contribution was greater for forced marching compared to running. The forced marching pattern demonstrates joint kinetics that may be more deleterious with prolonged exposure. Likewise, forced marching induced KAM% similar to those already suffering from knee OA.